2019
DOI: 10.1186/s13662-019-2351-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the spread of porcine reproductive and respiratory syndrome virus (PRRSV) in a swine population: transmission dynamics, immunity information, and optimal control strategies

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is an important swine disease that affects many swine industries worldwide. The disease can cause reproductive failure and respiratory problems in a swine population. As vaccination is an important tool to control the spread of PRRS virus (PRRSV), we employ a mathematical model to investigate the transmission dynamics of PRRSV and the effects of immunity information, as well as vaccination control strategies. We also explore optimal vaccination coverage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The important contribution of the local transmission route in spreading PRRSV into sow, GDU and finisher farms was consistent with previous studies, which demonstrated that farms located close to infected sites were more likely to report PRRSV outbreaks (Velasova et al, 2012; Phoo-ngurn et al, 2019; Silva et al, 2019; Jara et al, 2020), while others suggested that contact networks was the preferred transmission route (Amirpour Haredasht et al, 2017; Lee et al, 2017; Bastard et al, 2020; VanderWaal et al, 2020). Our approach to model the local PRRSV spread was unique in that we considered the effect of vegetation around each farm location as a physical barrier against mainly airborne transmission (Van Ryswyk et al, 2019; Jara et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The important contribution of the local transmission route in spreading PRRSV into sow, GDU and finisher farms was consistent with previous studies, which demonstrated that farms located close to infected sites were more likely to report PRRSV outbreaks (Velasova et al, 2012; Phoo-ngurn et al, 2019; Silva et al, 2019; Jara et al, 2020), while others suggested that contact networks was the preferred transmission route (Amirpour Haredasht et al, 2017; Lee et al, 2017; Bastard et al, 2020; VanderWaal et al, 2020). Our approach to model the local PRRSV spread was unique in that we considered the effect of vegetation around each farm location as a physical barrier against mainly airborne transmission (Van Ryswyk et al, 2019; Jara et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The important contribution of the local transmission route in spreading PRRSV into sow, GDU and finisher farms was consistent with previous studies, which demonstrated that farms located close to infected sites were more likely to report PRRSV outbreaks (Jara et al, 2020;Phoo-ngurn et al, 2019;Silva et al, 2019;Velasova et al, 2012). Similarly, our result highlighted the importance of transmission by direct contact through pig movements, as pointed out by other studies (Amirpour Haredasht et al, 2017;Lee et al, 2017;VanderWaal et al, 2020).…”
Section: Contribution Of Transmission Routessupporting
confidence: 93%
“…Our model results also demonstrate that the success of combined control strategies hinges on their relative effectiveness. Whereas evidence to date suggests that pigs carrying two copies of the PRRS resistance alleles are fully resistant to PRRSV infection (i.e., effectiveness of gene editing = 1) ( 27 , 28 , 46 ), the effectiveness of existing PRRS vaccines is severely compromised among other factors by the limited cross-protectivity of a given vaccine to different PRRSV strains, resulting in vaccine efficacies below 50% ( 47 , 48 ), suboptimal vaccine administration ( 37 , 49 ), or host heterogeneity in vaccine responsiveness ( 50 ). In our model, elimination of PRRS falls out of reach for the less stringent unregulated and concentrated distribution scenarios if vaccine effectiveness drops below 50%.…”
Section: Discussionmentioning
confidence: 99%